Strategi Pengendalian Antrean Tidak Teratur dalam Sistem Layanan Kantin Kampus - Amenda Septiala Tarigan; Hilmana Radhia Putera; Redian Wahyu Elanda; Lilik Zulaihah (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2025)
Campus canteens are essential facilities supporting academic activities. However, during peak hours, issues such as disorganized queues and delayed order deliveries frequently occur. These conditions lead to a decrease in customer satisfaction and service efficiency. This community service activity aims to develop a queue management strategy to improve service quality in campus canteens. The methods used include direct observation, socialization, and training for canteen staff, as well as the implementation of a simple order identification system. The socialization of the “numbered tags” queue system to the vendors has been carried out as part of the efforts to enhance service efficiency and organization. Preliminary evaluations indicate that this system has the potential to reduce customer waiting times and improve service efficiency. The finding suggests that a simple technology approach based on a numbered system can be an effective solution for addressing disorganized queues and improving the quality of canteen services in the future. This finding provides a foundation for canteen managers in other educational institutions to implement similar systems.